Pulmonary Alveolar Proteinosis - Sandeep M Patel; Hiroshi Sekiguchi; Jordan P Reynolds; Michael J Krowka (Canadian Respiratory Journal)
Pulmonary alveolar proteinosis (PAP) is a disease of alveolar accumulation of phospholipoproteinaceous material that results in gas exchange impairment leading to dyspnea and alveolar infiltrates. There are three forms of PAP: congenital, acquired and idiopathic; of which the latter two are predominant in the adult population. Previous case studies have found that the acquired form can be secondary to various autoimmune, infectious, malignant and environmental etiologies. Recent advances in the understanding of the pathophysiology of PAP demonstrate that the idiopathic form is due to antigranulocyte macrophage-colony stimulating factor antibodies. Therapeutic targets that replace granulocyte macrophage colony stimulating factor or remove these antibodies are being actively developed. The current standard of care is to perform whole lung lavage on these patients to clear the alveolar space to help improve respiratory physiology. A case of PAP is reported, followed by a literature review on the diagnosis and management of this rare condition with the aim of increasing awareness among physicians when treating patients who present with alveolar infiltrates.